Intratumoral expression of FoxP3-positive regulatory T-cells in T-cell lymphoma: no correlation with survival. (3rd April 2019) - Lundberg, Josefine; Berglund, David; Molin, Daniel; Kinch, Amelie
Abstract: Background . In cancer, regulatory T-cells (Tregs) were previously believed to inhibit tumor immunity, leading to reduced survival. However, in hematologic malignancies, including T-cell lymphoma (TCL), a correlation between increased numbers of tumor-infiltrating Tregs and a favorable prognosis has been reported. We aimed to investigate the expression of the Treg biomarker forkhead box protein 3 (FoxP3) in TCL in immunocompetent individuals and explore a possible correlation to overall survival. Methods . In total, 35 diagnostic biopsies of TCL were stained using a FoxP3-specific monoclonal antibody (clone 236A/E7). Visual scoring was performed by counting positive cells in 15 high-power fields. Clinical data were collected retrospectively from medical records. Results . All the TCLs contained FoxP3 + cells, median 342 FoxP3 + cells/mm 2 (range 1–3047). The degree of intratumoral expression of FoxP3 varied between the different subtypes of TCL, with the highest frequency found in angioimmunoblastic TCL. The frequency of intratumoral FoxP3 + cells had no impact on overall survival; neither when using a cutoff value of 200 FoxP3 + cells/mm 2 ( P  = 0.84) nor with FoxP3 as a continuous variable ( P  = 0.63). Conclusions . Intratumoral Tregs are frequently found in TCL in immunocompetent individuals. In this heterogeneous group of TCL, there was no correlation between the density of intratumoral FoxP3 + cells and overall survival.